Extraction of Protein-Enriched Fractions from Sunflower and Hemp Seeds: Composition and Colloidal Stability of Less Refined Fractions as a Function of Initial pH - Simone Bleibach Alpiger; Sandra Beyer Gregersen; Amanda May Ellermann; Tenna Ji Jing Dissing; Milena Corredig (Future Foods)
Simultaneous extraction of oil and protein from oilseeds using aqueous extraction yields protein concentrates with less refined compositions. This work evaluated the effect of initial extraction pH on the composition, yield, and physicochemical properties of colloidal components extracted from hemp and sunflower seeds. Understanding these differences is crucial for implementation of these novel practices as a sustainable alternative to the current practices.Results showed no general trend in protein yield and purity as a function of pH for the two seeds. For sunflower seeds, the highest protein recovery (52 %) and purity (55 % dm) were achieved under alkaline conditions. In contrast, hemp seeds showed 30 % protein recovery and 42 % purity, with only yields depending on extraction pH. For both oilseeds, extraction pH influenced the colloidal assemblies of oleosomes and proteins, as shown by light scattering and confocal microscopy. These variations were attributed to compositional differences between the two seeds, leading to different interactions among the soluble carbohydrates, proteins, and oleosomes. These findings demonstrate that improving fractionation efficiency between proteins and oleosomes requires a better understanding of biomacromolecule interactions and their resulting functional colloidal structures, before full adoption of these new, less refined ingredients in food formulations.